(untitled) (Scientific journal of the Fergana State University, 2024)
Use of an Avio 200 ISP-OES inductively coupled plasma optical emission spectrometer, elemental composition and quantitative analysis of animal skin samples. Contains 44 macro- and microelements. The skins of sheep, calves and goats, studied as samples, meet the requirements of the state standard and do not have a dangerous impact on the environment and human health.